Lavratura de inventário com partilha de bens extrajudicial com menores - Barretto, Larissa Maia (2024)
Considering the various advantages of carrying out acts of civil life through extrajudicial means, among them, agility, practicality and legal security, the importance of the possibility of drawing up inventory and extrajudicial sharing of assets, involving minor heirs, given the aptitude of notaries to the drawing up of said instrument, as well as the speed of its development, through administrative means. Furthermore, it is worth highlighting the relevance of this research, both for society and the legal world, considering the constant state of mutability that human beings find themselves in and consequently, the necessary adaptations to Brazilian law, in order to diligently and effectively resolve all demands daily activities of its citizens, including the inventory and sharing of assets with minor heirs.